Fighting Hoax and Hate Speech by Strengthening The Spirit of Pancasila in Preventing Disintegration of The Nation - I Nyoman Budiana; I Made Warta (Sociological Jurisprudence Journal, 2019)
The notion of democracy is used by most of the countries in the world as a foundation in managing the country, it is also the choice of Indonesia after the reformation period in 1998 as stated in the amendment of the 1945 Constitution. Through democracy, people can control the government administration so that the government does not act arbitrarily. With democracy, people are also given the opportunity to participate in all aspects of development, guaranteed the freedom of association / assembly to express opinions on various matters in the government administration in accordance with the constitutional corridor. In practice, after 2 (two) decades of reformation, freedom in democracy has become an act that exceeds the limit. In the national life order in Indonesia today, there have been various hoaxes (false information), utterances of hatred on social media, anarchic behavior occurring in various places, even radicalism movements which allegedly want to destroy the ideology of Pancasila and replace it with other ideologies. In this study, there are two problems that will be discussed, namely legal policy in the prohibition of hoaxes and hate speech and the ideology of Pancasila in the prevention of hoaxes and hate speeches. Legal policies in the prohibition of hoax and hate speech are regulated in Article 28 paragraph (1) of Law Number 11 Year 2008 concerning Information and Electronic Transactions. Prohibition of hoaxes and hate speeches is also carried out in various laws and regulations in other countries. Hoaxes and hate speeches threaten the integrity of Indonesia. Therefore, to guard and care for the Republic of Indonesia to remain based on the ideology of Pancasila, the nation's commitment to defend Pancasila as a state ideology must be able to actualize the noble values contained in the principles of Pancasila in life as well as possible and committed to fight hoax, utterances of hatred, anarchic actions and radicalism by strengthening the spirit of Pancasila for every Indonesian person and encouraging various government agencies to uphold the concept of the rule of law in preventing the disintegration of the nation.